Drug-induced pancreatitis: a real-world analysis of the FDA Adverse Event Reporting System and network pharmacology - Xie, Hao; Jiang, Lin; Peng, Junya; Hu, Haoyang; Han, Meifen; Zhao, Bin (Frontiers in Pharmacology, 2025)
BackgroundDrug-induced pancreatitis is a rare disease but frequently reported, owing to the vast number of medications.AimTo summarize potential drugs causing pancreatitis and to speculate on underlying mechanisms.MethodsWe extracted more than 60,000 reports of pancreatitis submitted to the U.S. Food and Drug Administration Adverse Event Reporting System (January 2004 to March 2023). Data on patient age, sex, weight, time to onset, and outcome (death et al.) were collected. Disproportionality analysis was used in data mining to identify associations between drugs and pancreatitis events. Seven databases, commonly used for network pharmacology analysis, were searched to identify potential targets.ResultsOf 867 drugs with 3 or more reports, 101 drugs met all criteria using disproportionality analysis and indicated a potential risk of pancreatitis. The risk of 40 drugs had not been previously noted in “UpToDate” database. Patients taking the drugs had a similar sex distribution, were mostly 45–64 years old, and were heavier (median, 88 kg; P < 0.0001). The median time to onset was 199 days (interquartile range, 27–731.5). Ponatinib (16.48%), tigecycline (14.12%) and valproic acid (13.41%) had higher fatality rates. Potential targets related to pancreatitis were identified in 50 of the 101 drugs.ConclusionClinicians providing the 101 drugs for treatment should stay vigilant to detect pancreatitis early.